2007
DOI: 10.4049/jimmunol.178.3.1349
|View full text |Cite
|
Sign up to set email alerts
|

The p85α Regulatory Subunit of Class IA Phosphoinositide 3-Kinase Regulates β-Selection in Thymocyte Development

Abstract: We examined the role of class IA PI3K in pre-TCR controlled β-selection and TCR-controlled positive/negative selection in thymic development. Using mice deficient for p85α, a major regulatory subunit of the class IA PI3K family, the role of class IA PI3K in β-selection was examined by injection of anti-CD3ε mAb into p85α−/−Rag-2−/− mice, which mimics pre-TCR signals. Transition of CD4−CD8− double-negative (DN) to CD4+CD8+ double-positive (DP) thymocytes triggered by anti-CD3ε mAb was significantly impaired in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
(35 reference statements)
0
23
0
Order By: Relevance
“…This is also consistent with the increased basal-activating phosphorylation of Lck at Y394 in hnRNP Ldeficient cells compared with wt controls. It is known that Lck mediates activation of T cells through recruitment and phosphorylation of its substrates, such as ZAP70, but also activates PI3K (42)(43)(44)(45). Hence, the higher basal Akt and ERK phosphorylation and related increased proliferation rate observed in hnRNP L-deficient DN4 cells are likely to be a consequence of the aberrant Lck signaling in these cells.…”
Section: Discussionmentioning
confidence: 98%
“…This is also consistent with the increased basal-activating phosphorylation of Lck at Y394 in hnRNP Ldeficient cells compared with wt controls. It is known that Lck mediates activation of T cells through recruitment and phosphorylation of its substrates, such as ZAP70, but also activates PI3K (42)(43)(44)(45). Hence, the higher basal Akt and ERK phosphorylation and related increased proliferation rate observed in hnRNP L-deficient DN4 cells are likely to be a consequence of the aberrant Lck signaling in these cells.…”
Section: Discussionmentioning
confidence: 98%
“…Strikingly, p110δ-p110γ double-deficient mice show a dramatic reduction in thymocyte numbers caused by a block at the DN3-DN4 stage of development in addition to reduced DP cell survival [60, 61]. Pre-TcR signaling as this stage was mostly controlled by p85α and p110δ [62]. The unexpected redundancy between p110δ and p110γ therefore suggested that GPCRs may play a greater role at this developmental stage than previously appreciated.…”
Section: Pi3k In T Cellsmentioning
confidence: 99%
“…The PI3K is recruited to the membrane where it produces the phosphatidyl-inositol PIP3 by phosphorylating PIP2. PIP3 activates downstream genes with a plekstrin homology domain such as PDK1 and Akt (Shiroki et al, 2007). Akt, in turn, phosphorylates genes that regulate cell metabolism, cell cycle progression and survival, such as GSK3β, P27 and the death protein Bad.…”
Section: Biology Of Il-7 Signalingmentioning
confidence: 99%